(untitled) (Journal of Applied Learning and Teaching, 2022)
There is currently a research gap since no study systematically explored the factors impacting the performance of Bangladeshi university students, especially those studying economics. In this paper, we define and estimate an econometric model to explain the variation in the academic performance of undergraduate economics students. A student’s ability, effort and motivation, and household attributes explain significant variation in university economics students’ performance in semester final examinations. Among the ability variables, performance in previous semesters, higher secondary performance, English proficiency, having studied economics at the pre-university level, and having a science background come out as important determinants. Among the variables grouped as ‘effort and motivation,’ daily study time, the number of courses retaken, and best friend’s past performance matter significantly. Up to a certain level, students with higher household incomes tend to perform better. Also, students from the local district tend to outperform others. With a mandatory attendance policy, making a minimum percentage of attendance binding in place, attendance fails to register any substantial impact. Also, the endogeneity of attendance could not be established.